Amikacin induced Stevens Johnson syndrome and toxic epidermal necrolysis overlap: a rare case report - Chandu, C. Sai; Chandana, T.; Sakshi, R.; Geetha, Karra; Ramarao, T. (International Journal Of Community Medicine And Public Health, 2024)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are the most severe adverse drug reactions. They are characterized by necrosis and epidermal release in vesicobulosa skin, mucous orifice, and eyes, with more severe general symptoms. SJS/TEN-overlap syndrome is the term used to characterize situations where 10–30% of the body skin area is detached. TEN or SJS is one of the deadliest dermatological catastrophes. Despite being a rare condition, it frequently has a high death rate. Different types of purpuric macules or rounded patches with mucosal lesions are characteristic features of these type 3 hypersensitivity reactions. We are presenting a case of 50-year-old female patient brought to hospital on account of multiple black to red coloured raised lesions over body in the last 8 days. Patient was asymptomatic in the last 8 days after that patient noted red coloured lesions first over face followed by lower back, upper limb, lower limb followed by itching and Jiburning sensation all over the body. The patient had symptoms such as redness of eyes in the last 3-4 days, burning sensation and ulcers in mouth in the last 3-4 days. These symptoms developed day after she received amikacin. She was diagnosed with SJS-TEN overlap. This case highlights the precipitant of antibiotics for SJS. She was recovered completely after stopping the causative drug and treatment with Immunoglobulin with other symptomatic measures. The causative drug was found to be Amikacin and medicine taken for comorbid conditions like epilepsy, hypothyroidism and hypertension. Rarely, amikacin has been linked to a range of drug hypersensitivity reactions, including toxic epidermal necrolysis, Stevens-Johnson syndrome, and overlap between the two conditions.